KUALITAS PELAYANAN BERDAMPAK LANGSUNG TERHADAP KEPUASAN MAHASISWA DI POLITEKNIK LP3I JAKARTA - Rini Mardikawanty; Sudirman Sudirman (JURNAL LENTERA BISNIS, 2021)
This study aims to analyze the infuence of service quality toward satisfaction of student. This research was conducted in LP3I Polytechnic Jakarta Campus Kramat Raya. The population in this study is student of campus kramat. The samples were 85 paticipants by using probability sampling method which uses a simple random sampling. Then, the data are prosessed by multiple regression analaysis. The research analyse whether the dependent variable namely the service quality influence signicantly toward satisfaction of the students which is as the independent variable. The result of this reserch showed that sevice quality had significant influence toward satisfaction of student which is achieved 64,9%. The result of simultaneous testing showed that service quality had significant influence to toward satisfaction of student.Keywords: Service, Quality, Satisfaction